FIGURE 5 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 5. (A–N) Nucinella svalbardensis sp. nov. (A–D) Lateral views of holotype showing shape of the articulated internal mould, anterior adductor muscle scar and possible anterior pedal retractor scar, rounded posterior margin and fine radial striations on internal mould surface. (E) Dorsal view showing weakly opisthogyrate umbo and deep ligament pit on the posterodorsal margin. (F) Anterior view showing anterior adductor muscle scar projecting weakly beyond pallial line. (G) Lateral view showing commarginal ornament on external shell surface. (H–I) Dorsal view of partially articulated specimen showing length of the cardinal teeth and relation of the possible ligament to the cardinal dentition. (J–K) Lateral view of the cardinal part of the hinge plate showing arrangement and shape of the cardinal teeth. (L) Ventral view of silicone rubber cast of the dorsal margin of articulated internal mould showing sabre-shaped lateral teeth and interlocked cardinal teeth. (M–N) Silicone rubber casts of right valve internal moulds showing two lateral teeth. (O–Q) Dacromya chetaensis Sanin, 1976. (O–P) Lateral and dorsal views showing shape of internal mould, taxodont dentition, anterior and posterior adductor muscle scars. (Q) Posterodorsal shell margin showing weak growth lines. (R–T) Mesosaccella rogovi sp. nov. (R) Lateral view of holotype left valve shell surface showing characteristic growth-line deflections around the posterior margin and carina subparallel to the dorsal margin. (S–T) Lateral view of left valve internal mould showing anterior adductor muscle scar, weak posterior adductor muscle scar and pallial line. (A–F) PMO 217.171, (G) PMO 224.978, (H–I) PMO 225.042, (J–K) PMO 224.981, (L–M) PMO 217.217, (N) PMO 225.020, (O–P) PMO 217.581, (Q) PMO 226.600, (R) PMO 224.971, (S–T) PMO 217.229. Scale bars 5 mm. : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 15, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112